Post-Mortem High-Anion-Gap Metabolic Acidosis and Blood Formate Quantitation as Diagnostic Markers of Fatal Oplosan Intoxication: A Retrospective Diagnostic Accuracy Study at a Tertiary Forensic Center in Indonesia - Bambang Sutrisno; Sri Mulyati; Karina Chandra; Jason Willmare (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Bootleg liquor (oplosan) containing illicit methanol remains a leading cause of preventable forensic death in Indonesia, yet objective post-mortem biochemical diagnostic criteria are incompletely standardised. Methods: This retrospective diagnostic accuracy study evaluated post-mortem high-anion-gap metabolic acidosis (HAGMA) and blood formate quantitation as confirmatory markers of fatal methanol intoxication at Hospital X, Central Java, between January 2019 and December 2023. Medical examiner records, autopsy reports, and post-mortem biochemistry data from 120 adult decedents were reviewed: 74 confirmed methanol (oplosan) fatalities and 46 non-methanol metabolic acidosis deaths as the comparison group. The reference standard was post-mortem blood methanol >20 mg/dL with documented oplosan exposure history. Post-mortem blood formate was quantified by gas chromatography–flame ionisation detection (GC-FID). Sensitivity, specificity, PPV, NPV, and ROC analysis were performed with 95% confidence intervals by the Wilson score method. Results: Mean blood formate was 18.8 ± 4.9 mmol/L in the methanol group versus 1.2 ± 0.8 mmol/L in controls (p < 0.001). Post-mortem albumin-corrected anion gap was 28.7 ± 5.1 versus 14.2 ± 4.6 mmol/L (p < 0.001). Blood formate >2.0 mmol/L achieved sensitivity 100% (95% CI 95.1–100%), specificity 80.4% (95% CI 65.9–90.1%), and AUC 0.989 (95% CI 0.971–0.998). HAGMA achieved sensitivity 94.6% (95% CI 86.4–98.0%), specificity 91.3% (95% CI 78.2–97.0%), and AUC 0.976. Combined positivity yielded a specificity 100% and a PPV 100%. Multivariable logistic regression identified formate as the dominant independent predictor (OR 123.8, 95% CI 21.6–709.3). Conclusion: Post-mortem blood formate and HAGMA are highly accurate complementary markers for confirming fatal oplosan intoxication and should be incorporated into standardised Indonesian forensic autopsy protocols.